Rain Effect Frequency of Infiltration Rate and Infiltration Capacity in Common Soil: Laboratory Test with Rainfall Simulator - Nasruddin; Aso (Newinera Publisher, 2020)
Analyzing the Influence of Rain Frequency Infiltration Rate and Infiltration Capacity in Common Soil Type (Laboratory Testing Study With Rainfall Simulator). Infiltration is the flow of water into the ground through the soil surface. This process is a very important part of the hydrological cycle and in the process of transferring rain into the flow of water in the soil before reaching the river. Infiltration (infiltration rate and capacity) is influenced by various variables, including soil type, slope inclination, density and type of vegetation, soil moisture content, and rainfall intensity. This study aims to determine the effect of rainfall frequency on the infiltration rate and infiltration capacity on common soil types. This research is a type of laboratory experimental research, using rainfall simulator tool. The soil used in this study is common soil type. Furthermore, artificial rain was provided with intensity I5, I15, and I25 and performed infiltration rate reading on the Drain Rainfall Simulator. The rate and capacity of infiltration in common soils increase proportionally to the increased intensity of rainfall, the higher the intensity of rainfall the higher the infiltration occurring at the same level of rain frequency. The rate and capacity of infiltration in common soils decrease proportionally to the increasing frequency of rain, the more the frequency of rain the smaller the infiltration occurring at the same level of rainfall intensity